Analisis Konsep Keadilan, Kepastian Hukum dan Kemanfaatan dalam Pengelolaan Lingkungan (UINSI Samarinda, 2016)
Environmental management becomes the attention of environmental existence because the exploitation is always in contiguity with nature, including forest exploitation which has positive and negative effects. On the one hand, the forest provides economical growth, but it also brings the natural demage (environmental ecosystem) on the other hand. The legal norms become a border and a sign of legal subject flexibility at once for forest exploitation. According to Gustav Radburch, the purposes of law are fairness, certainty and usefulness; it will become the hope to create environmental management which has environmentally sound based on Law No. 32 of 2009 on the Protection and Environmental Management. This article uses a normative legal research based on legal system components including the structure, substance and legal culture. There are some rights and obligations in environmental management; the right to live in healty and good environment, and obligation to keep the environment as well as possible. Justice in environmental management can be actualized if rights and obligations are run inequilibrium. Whereas, the legal certainty lies in the rule of law that become the reference of legal subject to exploit the forest resources. The legal certainty can be run effectively if it supported by good law enforcement. The legal benefit is achieved when the domminant legal subject perceived to benefit happiness. Fairness, certainty and benefits provide significant functions to maintain the environmental management with environmentally sound. But it can not be implemented simultaneously because of different tasks and functions.